The Correlation Between Bronchopulmonary Dysplasia and Platelet Metabolism in Preterm Infants - Yan, Longli; Ren, Zhuxiao; Wang, Jianlan; Xia, Xin; Yang, Liling; Miao, Jiayu; Xu, Fang; Gao, Weiwei; Yang, Jie (Frontiers in Pediatrics, 2021)
Background: Platelets play an important role in the formation of pulmonary blood vessels, and thrombocytopenia is common in patients with pulmonary diseases. However, a few studies have reported on the role of platelets in bronchopulmonary dysplasia. Objective: The objective of the study was to explore the relationship between platelet metabolism and bronchopulmonary dysplasia in premature infants. Methods: A prospective case-control study was performed in a cohort of premature infants (born with a gestational age <32 weeks and a birth weight <1,500 g) from June 1, 2017 to June 1, 2018. Subjects were stratified into two groups according to the diagnostic of bronchopulmonary dysplasia: with bronchopulmonary dysplasia (BPD group) and without bronchopulmonary dysplasia (control group). Platelet count, circulating megakaryocyte count (MK), platelet-activating markers (CD62P and CD63), and thrombopoietin (TPO) were recorded and compared in two groups 28 days after birth; then serial thrombopoietin levels and concomitant platelet counts were measured in infants with BPD. Results: A total of 252 premature infants were included in this study. Forty-eight premature infants developed BPD, 48 premature infants without BPD in the control group who were matched against the study infants for gestational age, birth weight, and admission diagnosis at the age of postnatal day 28. Compared with the controls, infants with BPD had significantly lower peripheral platelet count [BPD vs. controls: 180.3 (24.2) × 109/L vs. 345.6 (28.5) × 109/L, p = 0.001]. Circulating MK count in the BPD group was significantly more abundant than that in the control group [BPD vs. controls: 30.7 (4.5)/ml vs. 13.3 (2.6)/ml, p = 0.025]. The level of CD62p, CD63, and TPO in BPD group was significantly higher than the control group [29.7 (3.1%) vs. 14.5 (2.5%), 15.4 (2.0%) vs. 5.8 (1.7%), 301.4 (25.9) pg/ml vs. 120.4 (14.2) pg/ml, all p < 0.05]. Furthermore, the concentration of TPO was negatively correlated with platelet count in BPD group with thrombocytopenia. Conclusions: Our findings suggest that platelet metabolism is involved in the development of BPD in preterm infants. The possible mechanism might be through increased platelet activation and promoted TPO production by feedback.